Respuesta:
Dado el tiempo que dan, es lo mejor que pude explicar. saludos
Explicación paso a paso:
a) [tex](\frac{7}{5})^{4} = \frac{7}{5}*\frac{7}{5}= \frac{49}{25}*\frac{7}{5}= \frac{343}{125}*\frac{7}{5}= \frac{2,401}{625}[/tex]
b) [tex](-\frac{8}{6})^{3}= -\frac{8}{6}*-\frac{8}{6}= \frac{64}{36}=\frac{32}{18}=\frac{16}{9}*\frac{8}{6}= -\frac{128}{54}=-\frac{64}{27}[/tex]
c) [tex](\frac{8}{2})^{2}*(\frac{8}{2})^{3}= \frac{64}{4}*\frac{128}{2}=1,024[/tex]
d) [tex](-\frac{4}{3})^{2}*(-\frac{4}{3})^{2}= \frac{16}{9}*\frac{16}{9}= \frac{256}{81}[/tex]
e) [tex](\frac{10}{7})^{8} / (\frac{10}{7})^{5} = \frac{100,000,000}{5,764,801}/ \frac{100,000}{16,807}= \frac{1,000}{343}[/tex]
f) [tex](-\frac{5}{4})^{12} / (-\frac{5}{4})^{8}= -\frac{244140625}{16777216} / \frac{390625}{65,536} = -\frac{625}{256}[/tex]